Deubiquitinating Enzyme: A Potential Secondary Checkpoint of Cancer Immunity - Huang, Xing; Zhang, Xiaozhen; Xu, Jian; Wang, Xun; Zhang, Gang; Tang, Tianyu; Shen, Xiaochao; Liang, Tingbo; Bai, Xueli (Frontiers in Oncology, 2020)
The efficacy of cancer immunotherapy depends on the fine interplay between tumoral immune checkpoints and host immune system. However, the up-to-date clinical performance of checkpoint blockers in cancer therapy revealed that higher-level regulation should be further investigated for better therapeutic outcomes. It is becoming increasingly evident that the expression of immune checkpoints is largely associated to the immunotherapeutic response and consequent prognosis. Deubiquitinating enzymes (DUBs) with their role of cleaving ubiquitin from proteins and other molecules, thus reversing ubiquitination-mediated protein degradation, modulate multiple cellular processes, including but not limited to, transcriptional regulation, cell cycle progression, tissue development, and antiviral response. Accumulating evidence indicates that DUBs also have the critical influence on anti-cancer immunity, simply by stabilizing pivotal checkpoints or key regulators of T cell functions. Therefore, this review summarizes the current knowledge about DUBs, highlights the secondary checkpoint-like role of DUBs in cancer immunity, in particular their direct effects on the stability control of pivotal checkpoints and key regulators of T cell functions, and suggests the therapeutic potential of DUBs-based strategy in targeted immunotherapy for cancer.